Characteristics of the thermoluminescence of Sm3+-doped P2O5-K2O-MgO-Al2O3-ZnF2 glass. (15th December 2018) - Thomas, Sunil; Chithambo, M.L.
Abstract: We report the thermoluminescence of Sm 3+ -doped P2 O5 -K2 O-MgO-Al2 O3 -ZnF2 glass. A glow-curve measured at 1 °C/s after beta irradiation to 10 Gy shows two peaks; a broad high intensity one at 214.0 ± 0.4 °C and a weaker intensity peak at 75.2 ± 0.8 °C. The dependence of peak position on partial heating as well as on irradiation suggest that the main peak at 214 °C is a combination of several overlapping peaks. The activation energy of the different components of the main peak, calculated using the initial-rise method, differ showing that the components are distinct. The reproducibility, fading and dose response were examined by considering the dominant component of the main peak. The intensity of the peak changes with heating rate in a manner consistent with thermal quenching. Highlights: Thermoluminescence of Sm 3+ -doped fluorophosphate glass is reported. Kinetic parameters including activation energy and frequency factor are reported. The thermoluminescence is affected by thermal quenching. Thermal quenching parameters have been determined.